Bibliometric Analysis of The Articles Published on Augmented Reality Between The Years of 2010-2021 - Aslanci, Seher; Bayrak, Alp (Tauladan Fathimah Azzahra, 2023)
This study presents the results of the bibliometric analysis of 862 articles scanned using the keyword “augmented reality” in the Wos database in the category of published articles in the field of education between the years 2010-2021. The data obtained was analyzed bibliometrically in order to find out the annual distributions of the published articles; the authors publishing the highest numbers of articles on the topic; the journals publishing the highest numbers of articles; the scientific productivity of the authors over time and their citation burst scores; the countries of the corresponding authors and their the scientific productivity; the map of author collaboration networks of the countries; word cloud; and the authors' collaboration network.